Synthesis, Characterization and Antibacterial Studies of 2-azetidinones Compounds Derived from Amoxicillin - Entesar Obeed AL-Tamimi; Raad Mahjoub Muslih; Khalida Ali Thejeel (College of Pharmacy / Mustansiriyah University, 2015)
In this study, the new azetidinones were synthesized from Schiff bases 2(a-j) that derived from amoxicillin (1) on treatment with chloroacetyl chloride in presence of triethylamine gave azetidinone 3(a-j). The structure of these compounds have been elucidated on the basis of their physical and spectral. Azetidinone  compounds were also screened for  their antibacterial activity against some bacterial species using amoxicillin as standard.